Design and rationale for the I nfluenza vaccination A fter M yocardial I nfarction (IAMI) trial. A registry-based randomized clinical trial - Fröbert, Ole, MD, PhD; Götberg, Matthias, MD, PhD; Angerås, Oskar, MD, PhD; Jonasson, Lena, MD, PhD; Erlinge, David, MD, PhD; Engstrøm, Thomas, MD, PhD; Persson, Jonas, MD, PhD; Jensen, Svend E., MD, PhD; Omerovic, Elmir, MD, PhD; James, Stefan K., MD, PhD; Lagerqvist, Bo, MD, PhD; Nilsson, Johan, MD, PhD; et al. (The American heart journal, 2017)
Background Registry studies and case-control studies have demonstrated that the risk of acute myocardial infarction (AMI) is increased following influenza infection. Small randomized trials, underpowered for clinical end points, indicate that future cardiovascular events can be reduced following influenza vaccination in patients with established cardiovascular disease. Influenza vaccination is recommended by international guidelines for patients with cardiovascular disease, but uptake is varying and vaccination is rarely prioritized during hospitalization for AMI. Methods/design The Influenza vaccination After Myocardial Infarction (IAMI) trial is a double-blind, multicenter, prospective, registry-based, randomized, placebo-controlled, clinical trial. A total of 4,400 patients with ST-segment elevation myocardial infarction (STEMI) or non-STEMI undergoing coronary angiography will randomly be assigned either to in-hospital influenza vaccination or to placebo. Baseline information is collected from national heart disease registries, and follow-up will be performed using both registries and a structured telephone interview. The primary end point is a composite of time to all-cause death, a new AMI, or stent thrombosis at 1 year. Implications The IAMI trial is the largest randomized trial to date to evaluate the effect of in-hospital influenza vaccination on death and cardiovascular outcomes in patients with STEMI or non-STEMI. The trial is expected to provide highly relevant clinical data on the efficacy of influenza vaccine as secondary prevention after AMI.